The Neoliberal Republic : Corporate Lawyers, Statecraft, and the Making of Public-Private France - France, Pierre, 1987-; Vauchez, Antoine (Book collections on Project MUSE., 2020)
"This book analyzes the encounter between the French state and neoliberalism, tracing out the new role of broker that corporate lawyers and law firms have played between markets, the state, and society. Based on extensive interviews and a collective biography of more than 200 individuals who moved across business, government, and politics, it documents the new circuits of circulation within French power elite"--